Controlled isolation and stabilisation of pure metastable carbamazepine form IV by droplet-confinement via a continuous manufacturing route. Issue 39 (16th September 2022) - Parkes, Alice; Ziaee, Ahmad; Walker, Gavin; O'Reilly, Emmet
Abstract : This study outlines a systematic approach to control the polymorphism of carbamazepine (CBZ) and isolate the metastable polymorph CBZ form IV as a function of droplet size using spray drying as a continuous method of manufacture. Abstract : This study outlines a systematic approach to control the polymorphism of carbamazepine (CBZ) and isolate the metastable polymorph CBZ form IV as a function of droplet size using spray drying as a continuous method of manufacture. In this controlled process, CBZ molecules were confined within spray dried droplets of specific size during the nucleation process to investigate the effect of confinement space on the polymorphic outcome.